Sigorta Sözleşmesinde Sigorta Edilen Menfaatin Sahibinin Değişmesi Durumu - Bağrıaçık, Safiye Nur (Seçkin Yayıncılık, 2016)
6102 sayılı Türk Ticaret Kanunu (TTK) madde 1470’te sigorta edilen menfaatin sahibinin değişmesi durumu düzenlenmiştir. İlgili düzenleme de aksi öngörülmediği takdirde sigorta edilen menfaatin sahibinin değişmesi durumunda sigorta sözleşmesinin sona ereceği ifade edilmiştir. Getirilen yeni düzenleme ile sigorta uygulaması ile paralellik sağlanmıştır.

Turkish Commercial Code (No. 6102) article 1470 has regulated change of insured the interest. In case of change of the regulation unless it is otherwise provided in the owner's interest to be insured has been expressed that terminated of the insurance contract. Brought by the new regulations (Turkish Commercial Code) to be consistent with the insurance application.
Change of the Insured Interest’s Holder in Insurance Agreement
Keywords: Türk Ticaret Kanunu; Sigorta hukuku; Menfaat sahibi; Mal sahibi; Menfaat sahibinin değişmesi; Turkish Commercial Code; Insurance Law; Insurable Interest; Property Owner; Change in Insurable Interest